Clustering Penerima Beasiswa Yayasan Untuk Mahasiswa Menggunakan Metode K-Means - Sudarsono, Bernadus Gunawan; Lestari, Sri Poedji (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Grouping of scholarship recipients Scholarship assistance will be made based on the accumulated value using clustering where the scholarship recipients will be given scholarships with different amounts and sizes, because scholarships from foundations are limited and have levels of distribution. The division of groups to students who receive scholarships from foundations uses the clustering method of data mining where the function of clustering is a cluster or the task of grouping something is using the clustering algorithm approach, namely the K-means algorithm. The results of this clustering show that students based on their groups are divided into four groups based on the number of criteria, the results of the grouping show the number and decision of the foundation on granting foundation scholarships to students.